Clinical, functional, and genetic characterization of chronic granulomatous disease in 89 Turkish patients - (:unkn) unknown (MOSBY-ELSEVIER, 2013)
Background: Chronic granulomatous disease (CGD) is a rare primary immunodeficiency disorder of phagocytes resulting in impaired killing of bacteria and fungi. A mutation in one of the 4 genes encoding the components p22(phox), p47(phox), p67(phox), and p40(phox) of the leukocyte nicotinamide dinucleotide phosphate reduced (NADPH) oxidase leads to autosomal recessive (AR) CGD. A mutation in the CYBB gene encoding gp91(phox) leads to X-linked recessive CGD. Objective: The aim of this study is to show the correlation between clinical, functional, and genetic data of patients with CGD from Turkey. Methods: We report here the results of 89 patients with CGD from 73 Turkish families in a multicenter study. Results: Most of the families (55%) have an AR genotype, and 38% have an X-linked genotype; patients from 5 families with a suspected AR genotype (7%) were not fully characterized. We compared patients with CGD according to the severity of NADPH oxidase deficiency of neutrophils. Patients with A22(0), A67(0) or X91(0) phenotypes with a stimulation index of 1.5 or less have early clinical presentation and younger age at diagnosis (mean, 3.2 years). However, in p47(phox)-deficient cases and in 5 other AR cases with high residual oxidase activity (stimulation index >= 3), later and less severe clinical presentation and older age at diagnosis (mean, 7.1 years) were found. Pulmonary involvement was the most common clinical feature, followed by lymphadenitis and abscesses. Conclusion: Later and less severe clinical presentation and older age at diagnosis are related to the residual NADPH oxidase activity of neutrophils and not to the mode of inheritance. CGD caused by A22(0) and A67(0) subtypes manifests as severe as the X91(0) subtype.
Keywords: Chronic granulomatous disease; dihydrorhodamine-1,2,3 assay; CYBB; CYBA; NCF1; NCF2; nicotinamide dinucleotide phosphate reduced oxidase; mean fluorescence intensity; stimulation index; TERM-FOLLOW-UP; MUTATIONS; FAMILIES; FEATURES; TURKEY